2003
DOI: 10.1159/000074315
|View full text |Cite
|
Sign up to set email alerts
|

Fluoreszenzdiagnostik mit 5-ALA-Thermogel bei zervikaler intraepithelialer Neoplasie

Abstract: Fragestellung: Die lokale Applikation von flüssigen Pharmaka vor die Portio uteri ist ein bisher ungelöstes Problem. Deshalb wurde die Pharmakokinetik und Selektivität von 5-Aminolävulinsäure (5-ALA) aus 5-ALA-Thermogel bei Patientinnen mit zervikaler intraepithelialer Neoplasie (CIN) evaluiert. Das neuartige Thermogel Pluronic F127, welches im kalten Zustand in flüssiger Form vorliegt, geht bei über 31°C in einen gelartigen Zustand über und gewährleistet so eine verbesserte Anhaftung von 5-ALA an die Portio. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Furthermore, this triblock copolymer made of polyethylene oxide (PEO) and polypropylene oxide (PPO) is known for its excellent compatibility with other chemicals and its high solubilization capacity for different drugs. It has therefore already been used successfully by Andikyan et al 11 for fluorescence photodiagnosis of CIN mediated by 5-ALA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this triblock copolymer made of polyethylene oxide (PEO) and polypropylene oxide (PPO) is known for its excellent compatibility with other chemicals and its high solubilization capacity for different drugs. It has therefore already been used successfully by Andikyan et al 11 for fluorescence photodiagnosis of CIN mediated by 5-ALA.…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons observé une intensité fluorescente plus importante des lésions CIN, en comparaison avec le tissu épithélial adjacent. Ce résultat a déjà été décrit par Andikyan et al [15]. Ils ont aussi observé que la sélectivité de la fluorescence était supérieure pour les CIN3.…”
Section: Discussionunclassified
“…One study showed that the adhesion of 5-ALA solution can be improved by using a special thermogel (Lutrol F-127, thermolabile bioadhesive 19% poloxamer 407 gel), which is liquid at 4 1C and sticky at temperatures 431 1C [4]. The selectivity ratio between CIN 3 and normal tissue reached 3.5 after 2 h of incubation time [4].…”
Section: Fluorescence Diagnosis Of Cinmentioning
confidence: 99%